Germplasm for dairy development in East Africa: Phase 1 - identifying appropriate germplasm and delivery mechanisms - International Livestock Research Institute (International Livestock Research Institute, 2011)
The Dairy Genetics East Africa (DGEA) seeks to determine the most appropriate genotypes for the range of dairy production systems and levels of production operated by smallholder farmers in East Africa and how these genotypes can be multiplied and delivered to smallholders.